2002
DOI: 10.1354/vp.39-2-269
|View full text |Cite
|
Sign up to set email alerts
|

Encephalomyelitis Associated with Akabane Virus Infection in Adult Cows

Abstract: Abstract. Between August and September 2000, five 2-7-year-old cows in Korea exhibited neurologic signs and were diagnosed as infected with Akabane virus based on the results of histopathology, immunohistochemistry, serology, and reverse transcription polymerase chain reaction (RT-PCR) analysis. Immunohistochemistry and RT-PCR were equally effective and sensitive for diagnosing Akabane virus infection during the early stage of infection. Typical lymphohistiocytic inflammation characterized by perivascular mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 15 publications
2
33
0
Order By: Relevance
“…Encephalomyeltis associated with Akabane virus infection was noted in adult cows between August and September 2000 [15]. While the outbreak subsided by the end of October 2000, a marked increase in the incidences of bovine abortion due to Akabane virus infection was observed during the fall of 2000 and early spring of 2001, which indicates a hematogenous spreading of virus from the infected dam to the fetuses.…”
Section: Discussionmentioning
confidence: 97%
“…Encephalomyeltis associated with Akabane virus infection was noted in adult cows between August and September 2000 [15]. While the outbreak subsided by the end of October 2000, a marked increase in the incidences of bovine abortion due to Akabane virus infection was observed during the fall of 2000 and early spring of 2001, which indicates a hematogenous spreading of virus from the infected dam to the fetuses.…”
Section: Discussionmentioning
confidence: 97%
“…These arthropod-borne viruses (arboviruses) are widely distributed from the tropical to temperate zones of the world and have been associated with hematophagous arthropod vectors such as Culicoides biting midges and mosquitoes. The particular vector species linked to the Akabane virus (AKAV) and bovine ephemeral fever virus (BEFV) are C. brebitarsis, C. oxystoma, C. nebuchlsus and C. nipponensis (Lee et al, 2002;Hsieh et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The S segment RNA contains nucleotides encoding two proteins, nucleoprotein (N) and nonstructural proteins (Elliott et al, 1990). Since the AKAV was first isolated in Japan in 1959, several Asian countries including Korea have reported outbreaks of AKAV infection in ruminant (Akashi et al, 1997;Bak et al, 1980;Lee et al, 2002;Liao et al, 1996;Nakajima et al, 1980). Therefore, there have been efforts to prevent Akabane disease with several kinds of vaccines in Korea (Kim et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that AKAV and, recently, also the Aino virus (AINV) [13,14] cause teratogenic malformations when susceptible pregnant ruminants are infected [15][16][17]. AKAV was identified, serologically or by virus isolation, in Japan, Korea, Taiwan, Israel, Turkey, and Australia [1,4,6,7,9,[16][17][18][19][20][21] The virion is enveloped and the genome consists of three segments of ss RNA of negative polarity. The small (S) segment RNA is 858 bases long and encodes two proteins: the nucleocapsid and non-structural proteins.…”
Section: Introductionmentioning
confidence: 99%